Eye stroke protocol in in the emergency department - Bénard-Séguin, Étienne; Nahab, Fadi; Pendley, Andrew M.; Rodriguez Duran, Mariana; Torres Soto, Mariam; Keadey, Matthew; Wright, David W.; Newman, Nancy J.; Biousse, Valérie (Journal of stroke and cerebrovascular diseases, 2024)
•Fundus photography in the emergency department accelerates the diagnosis of retinal ischemia.•Optical coherence tomography of the retina is a powerful tool to detect early retinal ischemia.•An eye stroke protocol allows for rapid intervention for patients with acute retinal ischemia.•Education is needed so that acute vision loss patients present to the emergency department promptly. Visual outcomes of acute central and branch retinal artery occlusions (CRAO/BRAO) are poor and acute treatment options are limited by delayed diagnosis. In the hyper-acute setting, the ocular fundus may appear “normal”, making recognition challenging, but is facilitated by retinal optical coherence tomography (OCT), which is seldom available in emergency departments (ED). We evaluated the use of non-mydriatic ocular fundus photographs (NMFP) combined with OCT to facilitate ultra-rapid remote diagnosis and stroke alert for patients with acute vision loss presenting to the ED. Prospective evaluation of all CRAO/BRAO between 06/06/2023-06/06/2024 who had NMFP-OCT in our general ED affiliated with a stroke center. Over 1 year, 22 patients were diagnosed with CRAO, 4 with BRAO. Five patients presented within 4.5 hours of vision loss onset, 6 within 4.5 to ≤12 hours and 15 within >12 to 24 hours. On average, NMFP-OCT was performed within 141 minutes of presentation to the ED (range 27- 422 minutes). Diagnosis of acute RAO was made remotely with NMFP-OCT within 4.5 hours in 4 patients, 2 of whom received intravenous thrombolysis. Of the 9 patients with NMFP-OCT within 12 hours of symptom onset, 5 patients had subtle retinal whitening on color fundus photograph, but all had OCT inner retinal hyper-reflectivity/edema. Implementation of NMFP-OCT in a general ED enables rapid remote diagnosis of CRAO/BRAO and facilitates initiation of an eye stroke protocol in acute patients. OCT complements color fundus photography and provides greater diagnostic accuracy in hyperacute cases with near-normal appearing ocular fundi.